Additional Readings from Online Resources for 1st Grade of Elementary School Students - Pratiwi, Anggun Kartika Setyaning; Farida, S.Pd., M.Pd., Alief Noor (Bookchapter English Language Teaching, Literature, and Translation, 2025)
This study analyzes the alignment between digital reading materials on Let's Read Asia and LiteracyCloud.org with the literacy development needs of first-grade elementary school students based on Indonesia’s Emancipated Curriculum. Using a qualitative descriptive method, selected texts from the two platforms were examined for their relevance to foundational literacy competencies, including vocabulary development, reading comprehension, and phonemic awareness. The findings reveal that the texts demonstrate strong alignment with the curriculum regarding linguistic simplicity, contextual relevance, visual support, and the promotion of character values consistent with the Profil Pelajar Pancasila. These reading materials are also categorized by literacy level and freely accessible, supporting inclusive and equitable education. The discussion confirms that the results are consistent with previous studies highlighting the effectiveness of digital picture storybooks in enhancing early reading motivation and comprehension. Therefore, Let’s Read Asia and Literacy Cloud are valuable supplementary resources to support early literacy instruction in line with the Emancipated Curriculum.